2013 10th IEEE International Conference on Advanced Video and Signal Based Surveillance 2013
DOI: 10.1109/avss.2013.6636634
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a monitoring system for event recognition of older people

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 9 publications
2
13
0
Order By: Relevance
“…The study's results were consistent with those pre-432 viously presented in [32], where a recall of 88.…”
supporting
confidence: 88%
“…The study's results were consistent with those pre-432 viously presented in [32], where a recall of 88.…”
supporting
confidence: 88%
“…Constraints provide a generic basis to combine different sources of knowledge [ 8 , 9 ]. They can be handcrafted by domain experts [ 3 , 4 , 8 ], learned from data or obtained by a combination of both forms [ 9 ]. Knowledge-driven methods are generally associated to an ontological formalism to define domain concepts and their interrelations [ 8 , 10 ].…”
Section: Related Workmentioning
confidence: 99%
“…Prior work on knowledge-driven methods and color-depth sensing (e.g., Asus Xtion PRO Live) have demonstrated the benefits of this sensing approach (3D information about the scene and invariance to illumination changes) to track the position of hands and facial features during psychomotor exercises (cognitive rehabilitation) [ 6 ], to recognize fall events in hospital rooms [ 13 ], and to recognize complex daily living activities of senior people (e.g., making the bed). Finally, Crispim-Junior et al [ 3 ] compared the performance of event recognition between two different vision pipelines: a standard, color video camera and a color-depth sensor (Kinect ® with PrimeSense library). They have demonstrated that a pipeline with a standard color camera demanded a finer parameter tuning to handle low-level noise and achieve a performance comparable to the color-depth one.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations